Modification of chitosan-Fe3O4 microspheres with isophorone diisocyanate and formation of polyurethane/mchitosan-Fe3O4 antimicrobial polymer. Issue 12 (13th August 2018) - Song, Mengmeng; Xie, Jingang; Fu, Heqing
ABSTRACT: Polyurethane/modified chitosan-Fe3 O4 (PU/mCS-Fe3 O4 ) nanocomposites were prepared by incorporating chitosan-Fe3 O4 (CS-Fe3 O4 ) into PU through chemical grafting using isophorone diisocyante (IPDI). The isocyanate group of IPDI was introduced on the surface of CS-Fe3 O4 nanocomposites. The chemical functionalities of the CS-Fe3 O4 and mCS-Fe3 O4 were verified by Fourier-transform infrared and X-ray diffraction. The structure and properties were confirmed by scanning electron microscope, vibrating sample magnetometer, thermogravimetric analysis, atomic force microscope, and tensile testing. The experimental results indicate that thermal stability, tensile strength, and storage modulus of nanocomposites were improved with the increasing content of mCS-Fe3 O4 . Meanwhile, PU/mCS-Fe3 O4 nanocomposites have less cytotoxicity and good antibacterial activities against Escherichia coli and Staphylococcus aureus . GRAPHICAL ABSTRACT: